The principal neutralization determinant of simian immunodeficiency virus differs from that of human immunodeficiency virus type 1. - Javaherian, K (1992)
To identify the principal neutralization determinant (PND) of simian immunodeficiency virus (SIV), antisera were generated using recombinant gp110 [the SIV analog of the human immunodeficiency virus type 1 (HIV-1) external envelope glycoprotein, gp120], gp140, several large recombinant and proteolytic envelope fragments, and synthetic peptides of the SIVmac251 isolate. When purified under conditions that retain its native structure, gp110 bound CD4 and elicited antisera that neutralized SIVmac251 with high titer. Native gp110 also completely inhibited neutralizing antibody in sera from SIVmac251-infected macaques. In contrast, denatured gp110 and gp140, large envelope fragments, and synthetic peptides (including peptides analogous to the HIV-1 PND) elicited very low or undetectable neutralizing antibody titers and did not inhibit neutralizing antibody in infected macaque sera. Enzymatically deglycosylated gp110 efficiently absorbed neutralizing antibodies from macaque sera, showing that neutralizing antibodies primarily bind the protein backbone. A 45-kDa protease digest product, mapping to the carboxyl-terminal third of gp110, also completely absorbed neutralizing antibodies from infected macaque sera. These results show that the PND(s) of this SIV isolate depends on the native conformation and that linear peptides corresponding to the V3 loop of SIV envelope, in contrast to that of HIV-1, do not elicit neutralizing antibody. This may affect the usefulness of SIVmac for evaluating HIV-1 envelope vaccine approaches that rely on eliciting neutralizing antibody.